2017
DOI: 10.3126/jpn.v7i1.16942
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of hysterectomy specimens: one year study

Abstract: Background:The uterus is prone to develop several non-neoplastic and neoplastic conditions during the life time of a woman. The aim of this study is to study the histopathological features of varied uterine lesions, their profile and distribution of different lesions in relation of age. Materials and Methods:This is a histopathological database analysis of hysterectomy specimen of one year 2011/12 in Patan Hospital. The variables studied were age and histopathological diagnosis. SPSS version 16 was used as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 3 publications
7
10
0
Order By: Relevance
“…In the present study half of the patients 50.8% were seen in the age group of 40-49 years. The commonest surgical approach in the present study is abdominal hysterectomy (69.4%) followed by vaginal hysterectomy (32.6%) which is similar to other studies [8,12]. All vaginal hysterectomy was performed for uterine prolapse.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study half of the patients 50.8% were seen in the age group of 40-49 years. The commonest surgical approach in the present study is abdominal hysterectomy (69.4%) followed by vaginal hysterectomy (32.6%) which is similar to other studies [8,12]. All vaginal hysterectomy was performed for uterine prolapse.…”
Section: Discussionsupporting
confidence: 85%
“…All cases of uterine prolapse were presented with second and third degree of utero-vaginal prolapse. Baral R et al observed 56 (21%) cases of uterine prolapse [12].…”
Section: Discussionmentioning
confidence: 97%
“…This relatively high frequency of leiomyomas in our study is consistent with studies conducted by Pathak V et al 14 and Baral R et al, 3 both of whom found 49.78% and 48.6% frequency of leiomyoma respectively. In contrast lower values were observed in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…2 Hystrectomy is undertaken for varying indications and is among those gynecological surgeries that are carried out very often all over the globe, to effectively cure many gynecological conditions or save life of women suffering from postpartum hemorrhage in case of obstetrical hystrectomy. 3,4 Hystrectomy is a major surgical procedure enabling increased satisfaction and improved quality of life post-surgery despite its associated complications. 5,6 According to literature by age of sixty around 20% of women had underwent surgical removal of uterus and almost 40% among them diagnosed with abnormal uterine bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…Baral R et al 12 Adenomyosis is the second most common myometrial pathology in this study. Adenomyosis is rarely diagnosed preoperatively and is still largely underdiagnosed as it has no specific symptoms of its own.…”
Section: Methodsmentioning
confidence: 99%